Making Culture Count
XVIII, 304 p.
Keywords: This book is a collection of diverse essays by scholars, policy-makers and creative practitioners who explore the burgeoning field of cultural measurement and its political implications. Offering critical histories and creative frameworks, it presents new approaches to accounting for culture in local, national and international contexts.